Framework analítico de custo benefício relativo ao impacto das agências de desenvolvimento regional - Druciaki, Felipe Polzin (2023)
Regional development is a dynamic, complex and multifaceted process. It depends on various actors and institutions that form the context of a given location. To improve this process, it is essential to evaluate and measure the actions and results generated by the institutions involved in order to improve people's quality of life. In this way, this thesis seeks to help fill a theoretical-methodological gap regarding the evaluation of an institutional arrangement using a cost-benefit analysis model, and therefore seeks to answer what method and data are necessary to evaluate a Regional Development Agency in relation to its cost-benefit? To this end, the objective was to build and structure a framework that can evaluate the cost-benefit relationship of the actions contained in the planning of an institutional arrangement aimed at regional development, and in this way help to fill the existing theoretical gap with regard to this type of method used for this purpose. As a methodology, we chose to carry out a systematic survey using the Proknow-C method. Subsequently, the complete participatory cost-benefit analysis model was structured, as well as the construction and application of the structured questionnaire that make up the framework. The results showed that the proposed model can be used by an institutional arrangement to evaluate the relationship between cost and benefit, however the construction and operationalization of the method must follow the technical and conceptual protocols in the literature. The biggest challenge in conducting the model was the monetization of intangible situations based on the participation and response of the actors involved. The proposed model may shed light on an extremely important issue in the debate on regional development and institutional economics, which is their evaluation based on a cost-benefit analysis method.